An Integrated Perspective on Virulence-Associated Genes (VAGs), Antimicrobial Resistance (AMR), and Phylogenetic Clusters of Pathogenic and Non-pathogenic Avian Escherichia coli - Rezatofighi, Seyede Elham; Najafifar, Arash; Askari Badouei, Mahdi; Peighambari, Seyed Mostafa; Soltani, Mohammad (Frontiers in Veterinary Science, 2021)
Avian pathogenic Escherichia coli (APEC) is an important bacterial pathogen that causes avian colibacillosis and leads to huge economic losses in the poultry industry. Different virulence traits contribute to pathogenesis of APEC infections. In the present study, we aimed to investigate the presence of virulence associated genes (VAGs) and antimicrobial resistance (AMR) among two groups of APEC and avian fecal E. coli (AFEC) strains from apparently healthy birds and identify any associations among VAGs, AMR, phylogenetic groups. E. coli from birds with colisepticemia and yolk sac infection (YSI) (APEC), plus E. coli strains from the feces of healthy birds (AFEC) were compared by their content of VAGs, antimicrobial susceptibility patterns, and assignment to phylogenetic groups. In addition, isolates were fingerprinted using Enterobacterial repetitive intergenic consensus PCR (ERIC-PCR). All strains were susceptible to fosfomycin, ceftriaxone, and cefixime, while resistance rate to other tested antimicrobials was more than 50% except for gentamicin and furazolidone. All strains (except two) harbored at least three or more VAGs. tonB, csg, and iutA were the genes most commonly identified occurring with a prevalence of 99, 96, and 83% respectively. All phylogenetic groups were found in isolates from YSI, colisepticemia and the feces of healthy birds; however, the frequency of phylogroups varied according to the source of the isolate. B1 and C phylogroups were statistically more likely to be found among APEC from YSI and colisepticemic E. coli groups, respectively, while phylogroup A was the most frequently occurring phylogroup among AFEC strains. Our findings further revealed that AMRs and VAGs were common among E. coli isolated from poultry in Iran; however, the association between VAG and AMR was not direct in most instances that may reflect different evolutionary pathways conferring resistance and virulence. Exceptionally, strains related to phylogenetic group C had higher virulence and AMR compared to other groups that indicates the importance of this phylogroup. To some extent, ERIC-PCR was able to group strains by isolation source, phylogroup, and other traits; therefore, it may prove useful in primary classification of APEC strains.